Análisis del valor en el procesamiento de la carne de cerdo de la microempresa La Berna del cantón Portoviejo - Zambrano Mendoza, Luccy Elena (2020)
The development of the research was carried out in the city of Portoviejo, province of Manabí, which aims to apply the analysis of the value in the processing of pork from the La Berna microenterprise of the Portoviejo canton so that it positively impacts in its competitiveness, for this the data collection techniques were the interview and the survey directed to the owner of the microenterprise, local butcher shops and a sample of 383 inhabitants, to know the main indicators to optimize the quality in the pork meat that It is offered, but the consensus technique to the experts, being the basis for making matrices that support the work done. Among the main results obtained during the study period, was identifying that La Berna does not have a vacuum package, thus limiting the product offered by a retail market, and in consequence the level of competitiveness of the microenterprise is low, so it is advisable to add aggregate values to the product as such. In another sense to consider physical attributes, quality functions and brand that differentiate one product of another and in turn be able to meet the demand for consumption, in the near future to be representative in the sector where they operate.